Analisis Manajemen Pengelolaan Badan Usaha Milik Desa (BUMDES) Maju Jaya Di Desa Bulu Cina Kecamatan Hamparan Perak - Siti Fatimah (Yayasan Rahmat Islamiyah, 2023)
This study aims to determine the strategy for using the Maju Jaya BUMDes business unit to increase people's income, to determine the management of Maju Jaya BUMDes management to improve community welfare and to determine the supervision of Maju Jaya BUMDes to improve BUMDes performance. The research used is descriptive qualitative research. The data collection method used is the method of observation, interviews and documentation, conducted at BUMDes Maju Jaya in Bulu Cina Village, Hamparan Perak District. With several informants, namely the Village Head, Head of BUMDes, Treasurer, Management, BUMDes Supervisor and several communities. The results of this study indicate that based on the results of interviews by informants that the strategy used to increase people's income is to provide capital loans, improve services and improve the development of business units owned by BUMDes. BUMDes management has been implemented based on several stages in BUMDes management, namely planning, organizing, directing and supervising. But in organizing and supervising it cannot be said to be optimal in its development.